Analisis Hujah-Hujah al-Ghazali, Suhrawardi dan Sadr al-Din Shirazi Berkenaan Ontologi Mimpi : Analysis of The Arguments of al-Ghazali, Suhrawardi, and Sadr al-Din Shirazi Regarding the Ontology of Dream - Alias, Mohd Syahmir (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Dreams are phenomena that commonly occur during the sleep of humans and other mammals. Among those who have studied this phenomenon in depth are psychologists, neuroscientists, and philosophers. While modern psychologists and neuroscientists are primarily concerned with explaining the phenomenon of dreams itself, Islamic philosophers such as al-Ghazali regard dreams as a basis for arguing theological doctrines, including the reality of punishment in the grave. This perspective later drew the attention of later philosophers such as Suhrawardi and Sadr al-Din Shirazi, who further developed the theory. Accordingly, this article analyzes the arguments these three philosophers employ to articulate the ontology of dreams. To achieve this, document analysis is used to extract data from selected works of the aforementioned philosophers, followed by thematic analysis. At its core, the divergence in their arguments converges on the faculty of imagination (al-quwwah al-mutakhayyilah) as a shared conceptual foundation. The extended analysis of their views reveals implications for two central doctrines in Islamic theology: the truth of prophethood and eschatological events.